ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP INTERNET FINANCIAL REPORTING (STUDI EMPIRIS PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA TAHUN 2014) - Purbandari, Theresia; Immanuela, Intan (Widya Warta, 2018)
This study aimed to prove empirically that: company size, profitability, liquidity, leverage, and listing age have a positive effect on Internet Financial Reporting (IFR). The data were financial statements audited by companies listed on the Indonesia Stock Exchange until 2014. They were obtained from www.idx.co.id and www.sahamok.com. The sampling technique was purposive sampling and the data collected were 228 companies. Hypothesis testing used multiple linear regression analysis. The results of this study showed that firm size had a positive effect on IFR, while profitability, liquidity, leverage, and age of listing had no effect on IFR. The combination of firm size, profitability, liquidity, leverage, and listing age had an effect on IFR.